2019
DOI: 10.1155/2019/1796380
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effect of Confining Pressure on the Mechanics-Permeability Behavior of Mudstone under Triaxial Compression

Abstract: Injecting CO 2 into a reservoir disturbs the geostress field, which leads to variations in the permeability of caprock and affects its sealing performance. In this paper, the evolution characteristics of the permeability of Yingcheng mudstone were experimentally studied during deviatoric compression under different confining pressures. As the confining pressure increased, the strength of the mudstone increased bilinearly, the angle between the fault and the maximum principle stress increased, and the fault bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 66 publications
2
3
0
Order By: Relevance
“…In Fig. 13a, the results of the Malm carbonates, averaged for each rock type, show a good agreement between the maxima and minima of the range observed by different authors (Bakhtiari et al 2011;Dautriat et al 2011;Hassanzadegan 2013;Moosavi et al 2014;Teklu et al 2018;Meng et al 2019;Shi et al 2019). Some of the (dolomitic) limestone samples tend to have a high stress sensitivity of permeability and might be controlled by crack-like pores and microcracks (double-porous medium), while others exhibit a well-connected flow network that is more persistent to compressive stress (see Fig.…”
Section: Dependencies Of Different Rock Types Of the Malm Aquifersupporting
confidence: 77%
See 1 more Smart Citation
“…In Fig. 13a, the results of the Malm carbonates, averaged for each rock type, show a good agreement between the maxima and minima of the range observed by different authors (Bakhtiari et al 2011;Dautriat et al 2011;Hassanzadegan 2013;Moosavi et al 2014;Teklu et al 2018;Meng et al 2019;Shi et al 2019). Some of the (dolomitic) limestone samples tend to have a high stress sensitivity of permeability and might be controlled by crack-like pores and microcracks (double-porous medium), while others exhibit a well-connected flow network that is more persistent to compressive stress (see Fig.…”
Section: Dependencies Of Different Rock Types Of the Malm Aquifersupporting
confidence: 77%
“…Several authors observed a high variance of the stress sensitivity for different rock types (Fig. 13), even for rocks of similar lithology (Moosavi et al 2014;Blöcher et al 2014;Pei et al 2014;Meng et al 2019;Bakhtiari et al 2011;Hassanzadegan 2013;Shi et al 2019;Ghabezloo et al 2009a;Teklu et al 2018;Dautriat et al 2011). Considering the facies of the individual rock types, a general decrease in sensitivity to well-connected pore networks becomes apparent.…”
Section: Dependencies Of Different Rock Types Of the Malm Aquifermentioning
confidence: 94%
“…The exponential nature of the decrease in volumetric permeability of the Clashach sandstone samples (composed of 90% of quartz and 10% of feldspar) depending on the deformation and effective compressional pressure was revealed in [7]. An exponential dependence of permeability on effective rock pressure was also obtained in other previous experimental works [8][9][10][11][12][13].…”
Section: Introductionsupporting
confidence: 61%
“…The simplified exponential dependence of the porous media permeability on the effective pressure, established by the experimental studies [34][35][36][37][38][39]68,69], has the following form:…”
Section: Porous Rocksmentioning
confidence: 99%